Penerapan Decision Tree dalam Mendeteksi Pola Tingkat Stress Manusia Berdasarkan Pola Tidur Menggunakan Rapid Miner - Anshory, Ahmad Shofwan; Amali, Amali; Pratama, Fauzhan Qhof; Pikriyansyah, Ridho (Jurnal Pelita Teknologi, 2023)
According to data from the Health Service Monitor in 2023, stress is one of the most worrying health problems for 30% of respondents. Stress is often associated with sleep patterns. This study aims to identify the relationship between sleep patterns and stress levels in humans using 10 levels: 1-2 (normal), 3-4 (mild), 5-6 (moderate), 7-8 (high), 9-10 (very high). The model used in this study is decision tree, with data covering gender, age, occupation, sleep quality, physical activity level, BMI (Body Mass Index) category, blood pressure, heart rate, daily activities, and sleep disorders. This study is expected to provide valuable information on the relationship between sleep patterns and stress, so that strategies can be developed to improve sleep quality and reduce stress. Based on the data analysis, there are several factors that cause increased stress levels, namely blood pressure, sleep quality, body weight, gender, and daily activities. This can have a significant impact on sleep quality.